Pengelolaan Kedisiplinan Siswa Berbasis Pendidikan Islam (Studi Kasus Di Mtsn Susukan Kabupaten Semarang) - AZMI, Awaluddin, Prof. Dr. Yetty Sardjono, M.Si, Drs. Ahmad Muhibbin, M.Si (2015)
The purpose of this research are (1) To describe the characteristics of the student discipline based on Islamic education in MTsN Susukan. (2) To describe the management of student discipline based on Islamic education in MTsN Susukan. (3) To describe the management of student discipline based on Islamic education in terms of the type of leadership in MTsN Susukan headmaster. This type of research in this research is a qualitative research. The research design of this study is a single case study holistic. In this research, data collection techniques used (1) observation, (2) the method of interview (interview), and (3) documentation. Data analysis techniques in this research use a flow model analysis techniques, namely (1) data collection, (2) data reduction, (3) presentation of data, and (4) the conclusion. In this research to test the validity of the data used to test the credibility of the three kinds of triangulation, namely (1) triangulation of sources, (2) triangulation technique, and (3) triangulation of time. The results of this research relates to (1) The diversity of characteristics of student discipline based on Islamic education in MTsN Susukan that can be managed with strict rules and binding and based on Islamic education so as to create students who are discipline, characterized, insight, as well as faithful and devoted. (2) The management of student discipline based on Islamic education in MTsN Susukan can be managed with due regard to the functions and objectives of management and managed based on Islamic education so as to create a good student discipline management and can be implemented continuously. (3) The headmaster by the type of transformational leadership is able to deliver innovation, develop human resources, and build a collaborative culture in the management of student discipline based on Islamic education in MTsN Susukan.